List of unavailable infrasubspecific names originally published in Oberea Dejean, 1835, with nomenclatural notes on the genus (Coleoptera: Cerambycidae) - Li, Zhu; Cuccodoro, Giulio; Chen, Li (Zootaxa, 2015)
A list of 153 infrasubspecific and therefore unavailable names originally introduced in Oberea Dejean, 1935, is given. All were so far considered by previous authors to have been made available by Breuning in his 1960’s global key of the genus. Two of them (Oberea maculithorax v. pulla Matsushita, 1933 and Oberea suturalis v. flaveola Breuning 1960) refer to taxa in Obereopsis Chevrolat, 1855; and Leuconitocris Breuning, 1950, respectively.